2020
DOI: 10.1016/j.bbmt.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning Regimen of 5-Day Decitabine Administration for Allogeneic Stem Cell Transplantation in Patients with Myelodysplastic Syndrome and Myeloproliferative Neoplasms

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative treatment for patients with myelodysplastic syndromes (MDS) and myelodysplastic/myeloproliferative neoplasms (MDS/MPN). However, post-HSCT relapse remains a major cause of treatment failure. Here we assessed the efficacy of a new conditioning regimen comprising decitabine (Dec), busulfan (Bu), cyclophosphamide (Cy), fludarabine (Flu), and cytarabine (Ara-c) for allo-HSCT in patients with MDS and MDS/MPN. A total of 48 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…DAC can augment NK reactivity by activating the killer Ig-like receptor (KIR) on NK cells ( 33 ), therefore is associated with a low rate of leukemia relapse in allo-HSCT patients ( 34 , 35 ). Meanwhile, proper, but not excessive, NK cells exert greater clinical benefits in a DAC-involved conditioning therapy ( 36 ). The improved clinical benefits of the high-dose DAC schedule in this study might be highly correlated with synergistic effects of DAC and chemotherapy agents in killing leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…DAC can augment NK reactivity by activating the killer Ig-like receptor (KIR) on NK cells ( 33 ), therefore is associated with a low rate of leukemia relapse in allo-HSCT patients ( 34 , 35 ). Meanwhile, proper, but not excessive, NK cells exert greater clinical benefits in a DAC-involved conditioning therapy ( 36 ). The improved clinical benefits of the high-dose DAC schedule in this study might be highly correlated with synergistic effects of DAC and chemotherapy agents in killing leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hypomethylation therapy of 5-Aza combined with allo-HSCT may contribute to better aGvHD control after transplantation (6,(27)(28)(29)(30)(31)(32). The HMTi drug DZNep has also been proven to effectively prevent aGvHD in a mouse model (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, this could not be confirmed due to the limited number of cases in the current study. Recent studies have demonstrated that inclusion of decitabine in the conditioning regimen for allo‐HSCT in intermediate‐ and high‐risk MDS/AML patients may lower the incidence of acute GVHD 46,47 . The underlying mechanism may be associated with the induction regulatory T cells (Tregs) by decitabine 48 .…”
Section: Discussionmentioning
confidence: 99%